Clinical and behavioral conditions in oral health of volleyball and soccer athletes - Jullian Josnei de Souza; Juliana Squizatto Leite; Ricardo Bahls; Rodrigo Stanislawczuk Grande; Fabio André Santos (Universidade Estadual de Campinas, 2021)
Aim: In this cross-sectional study, we evaluated the oral hygiene habits, oral health conditions, and the perception about the influence of oral health conditions on the physical performance of youth and professional volleyball and soccer athletes. Methods: A total of 96 male athletes participated: 48 volleyball players (25 youth and 23 professional players); and 48 soccer players, of whom 22 were youth, and 26 were professional players. We analyzed the oral hygiene and oral health condition (daily toothbrush, flossing, mouthwash, dental plaque, orthodontic treatment, dental/facial trauma, temporomandibular dysfunction, malocclusion, and the athletes' perception about the influence of oral health conditions on the physical performance (yes or no)). Comparisons were made between the youth and professional athletes for each sport (volleyball and soccer). According to each variable, we applied the Chi-square, Fisher's Exact, and Mann-Whitney tests. Results: For soccer athletes, we found significant differences between youth and professionals for: flossing (p=0.014), orthodontic treatment (p=0.028), dental/facial trauma (p=0.041), and the athletes' perception about oral health and physical performance (p<0.001). Considering the category (youth and professional) regardless of the type of sport, we found significant differences for dental plaque (p=0.024) and dental/facial trauma (p=0.005). According to the sport (volleyball and soccer), independent of the category, we found significant differences for daily brushing, dental/facial trauma (p=0.005), and the athletes' perception about oral health and physical performance (p=0.006). Conclusion: We concluded that the surveyed athletes had good oral health and believed that oral health can influence sports performance.